Mega-events and the climate: what’s the game? - David Gogishvili; Martin Müller (Current Issues in Sport Science)
Introduction: The Olympics and the Men's Football World Cup are both significant carbon emitters, yet they hold potential for raising awareness and driving action on climate change (Chalip, 2006; Martiskainen & Sovacool, 2021). Due to their visibility and political leverage, these mega-events are expected to lead by example in combatting climate crisis. This study provides a coherent analysis of their carbon emissions, carbon intensity and the development of climate-related policies.